2021
DOI: 10.1111/ene.14795
|View full text |Cite
|
Sign up to set email alerts
|

Antiherpetic medication and incident dementia: Observational cohort studies in four countries

Abstract: Background and purpose Several epidemiological studies from Taiwan, all using the same data resource, found significant associations between herpes virus infection, antiherpetic medication, and subsequent dementia. We conducted a multicenter observational cohort study using health registry data from Wales, Germany, Scotland, and Denmark to investigate potential associations between antiherpetic medication and incident dementia, and also to comprehensively investigate such associations broken down according to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 22 publications
2
30
3
Order By: Relevance
“…Infection without antiviral treatment increases the risk somewhat. However, the results do not appear to be consistent across European countries (15) found in the brains of AD patients could protect against herpes simplex type 1 ( 16), and our finding that HZ vaccination reduces the risk of dementia is consistent with the link between viruses and AD, which might be mediated by inflammaging.…”
Section: Discussioncontrasting
confidence: 74%
“…Infection without antiviral treatment increases the risk somewhat. However, the results do not appear to be consistent across European countries (15) found in the brains of AD patients could protect against herpes simplex type 1 ( 16), and our finding that HZ vaccination reduces the risk of dementia is consistent with the link between viruses and AD, which might be mediated by inflammaging.…”
Section: Discussioncontrasting
confidence: 74%
“…Several 2D and 3D cell culture studies reported the use of antiherpetic agents to prevent HSV-1-induced AD-related neuropathology, including hippocampal damage (Ando et al, 2008;Wozniak et al, 2011Wozniak et al, , 2013Cairns et al, 2020). This is consistent with three large retrospective cohort studies spanning multiple countries showing that antiherpetic agents (e.g., acyclovir and valacyclovir) were associated with a reduced risk of dementia (Tzeng et al, 2018;Lopatko Lindman et al, 2021;Schnier et al, 2021). However, observational cohort studies can only inform associations, not causation.…”
Section: Discussionsupporting
confidence: 55%
“…In untreated patients, the risk of dementia increased by 50% compared to uninfected controls (Lopatko Lindman et al, 2021). A four-national (i.e., Wales, Scotland, Denmark and Germany) retrospective cohort study found that persons with HSV infection who were not given anti-herpetic medication had 18% higher risk of dementia compared to uninfected controls, although this effect was present in the Germany cohort only (Schnier et al, 2021). In a smaller retrospective cohort study comprising HSV-1-seropositive older adults, antiherpetic prescription was associated with 70% lower risk of AD development compared to no prescription (Hemmingsson et al, 2021).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…In vitro studies [ 24 27 ] have demonstrated that adding AHDs into a cellular medium inhibits the HSV-1-induced appearance of AD markers. Moreover, recent epidemiological results (mainly from medico-administrative databases) suggest a significant reduction in the risk of dementia in subjects infected with HSV or varicella-zoster virus (VZV) and treated with AHDs [ 28 33 ]. However, (i) the biological plausibility of the association found and (ii) potential indication or reverse causality biases have rarely been discussed.…”
Section: Introductionmentioning
confidence: 99%